The Body Size and Micronutrients Status Among the Bride-To Be in Probolinggo Districtof East Java (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2017)
Micronutrients deficiency is prevalent among women in reproductive age, particularly in developing countries, including in Indonesia. Small body size reflects a chronic deficiency of nutrients intake. Both of those problems may correlate each other and making maternal nutrition more complicated. Brides-to be are the most important group of women in reproductive age who require better recognition, because they will become mothers. This study was to describe inter-correlation among anthropometric indices which reflected the maternal body size and several indicators of micronutrient status. A cross sectional study was conducted in selected sub-districts of Probolinggo District, East Java Province year 2012. The samples size of 115 brides-to be were randomly selected from list of brides-to be in Sub-district Office of Religious Affair. The observed variables were body weight, height, body mass index (BMI), mid upper arms circumference (MUAC), micronutrients status including concentration of hemoglobin, serum ferritin, serum retinol and serum zinc. Pearson correlation test was used to analyze data using SPSS for Window version 13.0. Result showed that the average of body weight was 47,3 kg, average stature was 150,4 cm, BMI was 20, MUAC was 25,3 cm. The average of hemoglobin level was 12,4 g/dL, serum ferritin was 50,6 µg/L, serum retinol level was 1,06 µmol/L, and serum Zn level was 12,9 µmol/L. Statistical analisis showed significant correlation between the body weight and hemoglobin concentration (r =0,25, p = 0,01) and serum retinol (r = 0,21, p = 0,03); between BMI and hemoglobin concentration (r = 0,31, p = 0,00) and serum ferritin (r = 0,23, p = 0,03), and serum retinol (r = 0,21, p = 0,02); between MUAC and hemoglobin (r = 0,32, p = 0,00) and serum retinol (r = 0,24, p = 0,02); between hemoglobin concentration and serum ferritin concentration (r = 0,30, p = 0,00). Stature did not correlate with any indicators of micronutrient. It implies that among the indices of body size, body weight and BMI as well as MUAC are important indicators relating to iron status, and vitamin A status, but not zinc status.